Effect of Local Point Electroacupuncture with Balance Method on Waist Pain Scale in Farmers and Farm Laborers in Karanglo Village, Klaten - Nisrina Lam'a Aris Subagyo; Kurnia Eka Putri; Sholichan Badri (Indonesian Journal of Acupuncture, 2026)
Low back pain is one of the most common musculoskeletal disorders among farmers in Indonesia. This is related to unergonomic work positions, such as prolonged bending. Local point electroacupuncture therapy and the Balance Method are widely used as alternative treatment methods to help reduce pain and improve the quality of life and well-being of farmers. This study aims to determine the effect of local point electroacupuncture with the Balance Method on the scale of low back pain in farmers and hunters in Karanglo Village, Klaten. This study uses a type of quantitative research, a quasi-experimental design with a two-group pretest-posttest design. namely comparing 2 groups given different interventions. The research was conducted by measuring the initial NRS before being given the intervention (Pretest) and measuring the NRS value after being given the intervention (Posttest) with a purposive sampling method. The number of samples used was 40 research subjects, divided into two groups, namely the Balance Method group and the local point electroacupuncture group of 20 research subjects each. The Mann-Whitney test results showed a significance value of p > 0.05. This means that there is no significant difference between the two groups. The Balance Method group changes from a scale of 6 to 1, and the local point electroacupuncture group from a scale of 5 to 1. Both groups showed changes in the low back pain scale. Both groups are influential in reducing the scale of low back pain in farmers and farm laborers in Karanglo Village, Klaten